Aspectos epidemiológicos de aborto en mujeres atendidas Hospital Regional del Amazonas – Iquitos 1991 - Dávila Torres, Consuelo (1992)
They were prospectively studied 191 patients with a diagnosis of abortion in the regional hospital of the Amazon - Iquitos, 1991. The cases studied were divided into two groups according to the type of abortion presented, describing the epidemiological characteristics of these groups and the frequency and methods used for abortion. Both groups have similar epidemiological characteristics except more or less systemic involvement and mortality observed in induced abortions. The • frequency was higher in induced abortions than for spontaneous. • The average age was 26.5 years with a range between 15 to 44 years, registering an average parity of 3.8 for both groups. In the induced abortions dominated the cohabitation and single-grade secondary education and spontaneous cohabiting and married to the primary level. The highest percentage of women denied having had previous abortions; the interqenésico space in both groups was short and the number of family members was more than 5.For other hand, came from marginal urban areas, with an average socioeconomic status and were engaged in household chores. Finally to induce abortion the most widely used injectable were followed by the introduction of foreign bodies.